Health Sciences Librarianship's Status as a Profession Is Unclear, According to Its Members / Koenig, R. A., Rodriguez, V. A., & Sima, A. P. (2021). Attitudinal attributes of professionalism in health sciences librarians. Journal of Library Administration, 61(1), 1–20. https://doi.org/10.1080/01930826.2020.1845544 - Kaplan, Samantha J. (Evidence Based Library and Information Practice, 2023)
Objective – To determine health sciences librarians' attitudes toward professionalism and to examine relationships between professionalism attributes and participant characteristics as defined by the Richard H. Hall Professionalism Inventory.Design – Cross-sectional online survey using the Richard H. Hall Professionalism Inventory.Setting – Electronic mailing lists of the Medical Library Association (MLA), the Association of Academic Health Sciences Libraries (AAHSL), the Association of College and Research Libraries (ACRL) Health Sciences Interest Group, and the Canadian Health Libraries Association (CHLA).Subjects – There were 430 participants.Methods – The online survey, created in REDCap, was distributed electronically across multiple mailing lists during June and July of 2019. Quantitative analysis included descriptive statistics and ANOVA conducted in R with reliability determined by Cronbach's alpha.Main Results – Professionalism scores for health sciences librarians were lowest in public service and self-regulation, and highest in professional organization as referent, autonomy, and sense of calling. Individuals with a degree in health sciences scored lower on a sense of calling than individuals with Library and Information Science (LIS) degrees. Faculty benefits such as tenure decreased sense of calling. There were statistically significant differences according to role (e.g., archives, administration). Subject specialty librarians had lower scores in most attributes.Conclusion – Health sciences librarianship does not clearly meet the criteria of a profession. Its heterogeneity of specializations and receptiveness to diverse backgrounds and perspectives are possible threats to its ability to create a cohesive identity. Further, duties that can be considered non-library work appear to correlate with lower professionalism scores, even when they are associated with faculty status.